PELATIHAN KARYA TULIS ILMIAH BIDANG SAINS DATA BAGI GURU MADRASAH ALIYAH NEGERI (MAN) 2 NGANJUK - Athoillah, Muhammad; Fitriani, Fenny (Kanigara, 2024)
Scientific writing is not only a formal tool, but is an active step in exploring, processing and documenting knowledge in the field of data science. These skills are key in responding to business and social challenges that take advantage of abundant information. Therefore, the Training on Writing Scientific Papers in the Field of Data Science for MAN 2 Nganjuk teachers, which was organized by the Student Creativity Program Team (PKM) of PGRI Adi Buana University Surabaya, was based on the urgency to empower educators in conveying the concepts and application of data science . The training material includes basic data science concepts and practical guidance for writing scientific papers. Evaluation of participant satisfaction shows positive results, reflecting the effectiveness of the training and positive contribution to the development of science and technology in society.